Pelatihan Perangkat Pembelajaran untuk Guru PJOK Sekolah Dasar di Kota Kupang - Veramyta Maria Martha Flora Babang; Salmon Runesi; Maria Andriani Barek Ladjar; LUKAS MARIA BOLENG (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
The problem finding in partner schools of the Physical Education, Health and Recreation Study Program, Faculty of Teacher Training and Education, Nusa Cendana University is that there is no clear understanding of the making of learning tools based on the 2013 Curriculum for Elementary School PJOK teachers in Kupang City. PJOK teachers are not involved as instructors who train teachers, so the majority of PJOK teachers who take part in the training only make learning tools. This is an obstacle for PJOK teachers in the field if they are required to make learning tools according to curriculum expectations. So community service can be a solution for PJOK teachers. The implementation method in this Science and Technology for Society (IbM) activity starts from the preparation, implementation, mentoring and evaluation stages with the form of activities and methods and places used. The final results of IbM activities are able to produce uniformity of learning tools in this case the syllabus, lesson plans, KKM, Semester Programs, Annual Programs for Elementary School PJOK teachers.